Employers’ Attraction And Retention Of Older Workers: A Systematic Review - Samuels, Lea (Cranfield University, 2010)
The ageing of the population and the workforce has become a global phenomenon that has created concern about labour as well as skills shortages. Therefore the continuation of older workers in paid employment is regarded as beneficial to both the economy and to the older worker. The aim of this dissertation is to make an enquiry about what employers are doing to make themselves attractive to these older workers and how they are retaining the older workers already present in their organisations. The methodology has been to construct a review protocol through the formation of a review panel as well as the development of a detailed search strategy that included a transparent inclusion and exclusion criteria. The measurement for evaluating the quality of studies used in this systematic review is presented along with the strategy adopted to extract the data and synthesise the findings. The search results were quite limited due to the limited number of research studies conducted particularly for the first of the two research questions relating to the attraction of older workers into the organisation. However the studies that have been conducted thus far shows a level of connection between the methods that can be used to attract older workers and those identified as being used to retain older workers. Finally, gaps from the systematic review process are identified and further research areas suggested.
Keywords: Older Worker; Recruitment Attraction; Retention